Hubungan Mutu Pelayanan Keperawatan dengan Kepuasan Pasien di Ruang Rawat Inap Rumas Sakit Umum Daerah Embung Fatimah Kota Batam Tahun 2024 - Firda Rizki Ananda Dewi; Nelli Roza; Didi Yunaspi (Lembaga Pengembangan Kinerja Dosen, 2026)
Patient satisfaction is a subjective assessment of the quality of service received. Based on data from the Indonesian Ministry of Health in 2024, the level of public satisfaction with health services only reached 53.06%, while the Riau Islands Province Ombudsman report recorded 46% of public complaints related to government hospitals. One of the factors that influences patient satisfaction is the quality of nursing services. This study aims to analyze the relationship between the quality of nursing services and patient satisfaction in the inpatient ward of Embung Fatimah Hospital, Batam City in 2024. The research design used a cross-sectional approach with a sample size of 99 respondents selected through purposive sampling techniques. Data were collected using a questionnaire and analyzed using the Spearman's rho statistical test. The results showed a significant relationship between the quality of nursing services and patient satisfaction with a p-value = 0.001 (<0.05). Conclusion: The majority of patient satisfaction was 40 (40.4%). The quality of nursing services is mostly good, namely 39 (39.4%). There is a significant relationship between the quality of nursing services and patient satisfaction. The results of this study are expected to be input for hospital management, nurses, and policy makers to improve the quality of nursing services in order to increase patient satisfaction. In addition, these results can help increase public trust in health facilities.